2011
DOI: 10.1186/1756-0500-4-243
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the Corynebacterium pseudotuberculosis hsp60-hsp10 operon, and evaluation of the immune response and protective efficacy induced by hsp60 DNA vaccination in mice

Abstract: BackgroundHeat shock proteins (HSPs) are important candidates for the development of vaccines because they are usually able to promote both humoral and cellular immune responses in mammals. We identified and characterized the hsp60-hsp10 bicistronic operon of the animal pathogen Corynebacterium pseudotuberculosis, a Gram-positive bacterium of the class Actinobacteria, which causes caseous lymphadenitis (CLA) in small ruminants.FindingsTo construct the DNA vaccine, the hsp60 gene of C. pseudotuberculosis was cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…Hsp60 and Hsp10 form a folding cage through their rings and produce large and efficient protein-editing machinery that facilitates proper folding and assembly of mitochondrialimported proteins and corrects misfolded polypeptides (Hansen et al 2003;Magen et al 2008). Although the Hsp60/Hsp10 complex system has been well studied in many species; however, the regulatory mechanism of this system, especially in crustaceans, remains unclear (Costa et al 2011;Johnson et al 2014;Nisemblat et al 2014). The chaperon folding cage is composed of two parts: a dome-shaped heptameric ring of Hsp10 (GroES) subunits and Hsp60 (GroEL) cylinder with ATPase (Saibil and Ranson 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Hsp60 and Hsp10 form a folding cage through their rings and produce large and efficient protein-editing machinery that facilitates proper folding and assembly of mitochondrialimported proteins and corrects misfolded polypeptides (Hansen et al 2003;Magen et al 2008). Although the Hsp60/Hsp10 complex system has been well studied in many species; however, the regulatory mechanism of this system, especially in crustaceans, remains unclear (Costa et al 2011;Johnson et al 2014;Nisemblat et al 2014). The chaperon folding cage is composed of two parts: a dome-shaped heptameric ring of Hsp10 (GroES) subunits and Hsp60 (GroEL) cylinder with ATPase (Saibil and Ranson 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the economic [1, 2] and zoonotic [3] relevance of CL, a satisfactory vaccine model has not been developed [4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…Other advantages of DNA vaccine over conventional vaccines include no risk of infection as they are not likely to have any residual virulence associated with live attenuated strains, induction of long‐lived immune response, stability at low and high temperatures, easy preparation and low cost 41 , 42 , 43 . Direct Intramuscular injection of plasmid DNA encoding HSP60 of C. pseudotuberculosis has been reported to produce immune responses in mice 44 . Despite their multiple advantages, there are certain limitations of plasmid DNA vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43] Direct Intramuscular injection of plasmid DNA encoding HSP60 of C. pseudotuberculosis has been reported to produce immune responses in mice. 44 Despite their multiple advantages, there are certain limitations of plasmid DNA vaccines. Studies have revealed that antibody levels achieved using DNA vaccines are lower than conventional vaccines.…”
Section: Discussionmentioning
confidence: 99%